2013
DOI: 10.1007/s10552-013-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association between induced abortion and breast cancer risk among Chinese females

Abstract: IA is significantly associated with an increased risk of breast cancer among Chinese females, and the risk of breast cancer increases as the number of IA increases. If IA were to be confirmed as a risk factor for breast cancer, high rates of IA in China may contribute to increasing breast cancer rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
4
28
2
1
Order By: Relevance
“…However, most previous case-control studies have observed a positive association between induced abortion and breast cancer [21], whereas most cohort studies have not [22,23], suggesting that the increased risk observed in our and other case-control studies is likely to be due to recall bias. On the other hand, we observed a consistent protective effect for both rural and urban women undergoing spontaneous abortion.…”
Section: Discussioncontrasting
confidence: 80%
“…However, most previous case-control studies have observed a positive association between induced abortion and breast cancer [21], whereas most cohort studies have not [22,23], suggesting that the increased risk observed in our and other case-control studies is likely to be due to recall bias. On the other hand, we observed a consistent protective effect for both rural and urban women undergoing spontaneous abortion.…”
Section: Discussioncontrasting
confidence: 80%
“…These researchers also found evidence of a dose–response risk. At least two abortions increased the risk 76% and “at least at three” IAs increased the risk 89% (both results were highly significant, P  < 0.001) (Huang et al 2013).

India (2008)—Indian researchers reported that the mean number of abortions among cases of breast cancer was nearly twice that reported in controls (1.02 v. 0.52, t = 2.35, P  < .05) (Rai et al 2008).

…”
Section: Fact 8: There Is Worldwide Evidence For a Link Between Inducmentioning
confidence: 99%
“…For instance, the rural county of Qidong has a breast cancer incidence of 12.8 per 100,000 women, “which is approximately one-tenth that of white women in the United States” (Linos et al 2008). Nonetheless, “the incidence of breast cancer in China has increased at an alarming rate over the past two decades (from 36.17/100,000 to 51.24/100,000 in urban areas and from 10.39/100,000 to 19.61/100,000 in rural areas” (Huang et al 2013). Overall, Chinese incidence rates are expected to climb from the current 10–60 per 100,000 women to “more than 100 new cases per 100,000 women aged 55–69 years by 2021” (Linos et al 2008).…”
Section: Fact 8: There Is Worldwide Evidence For a Link Between Inducmentioning
confidence: 99%
See 1 more Smart Citation
“…More than one million new cases of breast cancer are diagnosed worldwide each year (Rana et al, 2013). In China, the incidence of breast cancer also had increased at an alarming rate over the past two decades (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%